Development of Ill-Structured Problem-Solving Skills Instrument Based on Local Socio-Scientific Issues (SSI) on the Topic of Environmental Pollution (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aimed to develop an assessment instrument to measure students’ ill-structured problem-solving skills using local socio-scientific issues (SSI) on environmental pollution. The research employed a Research and Development (R&D) model with four stages: (1) preliminary study, (2) item development, (3) expert validation, and (4) trial. The instrument was piloted with 120 chemistry education students from UIN Mataram and Universitas Pendidikan Mandalika in Indonesia. The final instrument consisted of 27 essay-based items mapped to four stages of ill-structured problem solving: 8 items for problem representation, 6 for solution generation and selection, 5 for justification, and 7 for solution monitoring and evaluation. Expert validation yielded a high construct validity index (CVI = 0.93). Readability analysis indicated that 75% of students found the language clear, 78% understood the visuals, and 70% were familiar with the chemical terminology. Results indicated that 17 items were of moderate difficulty, 7 were easy, and 3 were difficult. The instrument demonstrated high internal consistency, with a Cronbach’s Alpha value of 0.805. This instrument offers a valid and reliable tool for evaluating students’ engagement in authentic, context-rich chemistry problems. It supports chemistry educators in fostering critical thinking and scientific literacy by embedding local socio-scientific issues into semester-long instruction cycles.